Realizing the Pancasila Student Profile through SDG 4: Zero Waste, Science, and Literacy Projects in Elementary Schools - Husnul Fatihah; Dadang Sundawa; Vina Amilia (Journal of Current Studies in SDGs, 2027)
Objective: The study aimed to explore, analyze, and describe the strategies implemented by elementary schools to develop the Pancasila Student Profile. Specifically, the study examined school programs, stakeholder involvement, and institutional practices that support the internalization of Pancasila values and character development among students at Palembang Nature School. Method: The study employed a descriptive qualitative approach and was conducted at Palembang Nature School, also known as SAPA Palembang Elementary School. The research participants consisted of the principal, teachers, students, and parents or guardians. Data were collected through observations, interviews, and document analysis. The data analysis process involved data collection, data reduction, data presentation, and conclusion drawing. Data credibility was established through source and technique triangulation. Results: The findings identified five major programs implemented to develop the Pancasila Student Profile: (1) Zero Waste, (2) Science Project, (3) Language Literacy Week, (4) Cultural Week, and (5) Survival. These programs facilitated the development of students’ character, faith in God Almighty, knowledge, creativity, independence, responsibility, and democratic attitudes. The successful implementation of the Pancasila Student Profile was supported by three main factors. Novelty: The study provides an integrated description of how nature-based elementary school programs can be used to develop the Pancasila Student Profile through experiential, environmental, scientific, cultural, literacy, and survival-oriented activities. The findings demonstrate that the Pancasila Student Profile can be effectively developed through a whole-school approach involving school leaders, teachers, students, and parents.